Competences for strengthening entrepreneurial capabilities in Europe - Tatjana Ņikitina; Inga Lapiņa; Modris Ozoliņš; Madara Mara Irbe; Martijn Priem; Matthijs Smits; Mikhail Nemilentsev (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Authors in previous studies pointed out that the professional competences of managers overlap with the competences and skills that are attributed to entrepreneurs. The goal of this study is to analyze the correlation between the actual market demand for competences to develop new businesses and the competence of training and development by higher education institutions (HEIs) and business supporting institutions (BSIs). The research question is "Are the entrepreneurial competences demanded by the domestic markets in Finland, Latvia and The Netherlands aligned with the entrepreneurship educational and business supporting policies?" As a research methodology, we chose focus groups and semi-structured interviews conducted for start-up entrepreneurs, HEIs, and BSIs as methods for data gathering. An importance-performance analysis (IPA) was applied as the method for data analysis. As the main research results, the authors identified that ethical and sustainable thinking as well financial and economic literacy were considered to be the least important competences, while motivation and perseverance were commonly ranked as highly important by entrepreneurs in all the countries studied. Entrepreneurship education policy in The Netherlands is fully harmonized with market demand. Entrepreneurship development activities in Finland also meet the market's needs, however HEIs and BSIs could develop self-awareness and self-efficacy as well as cope with uncertainty, ambiguity and risk competences. The major disagreement was detected between entrepreneurs' expectations and entrepreneurship education activities conducted by HEIs and BSIs in Latvia. This research implication fills the gap in knowledge about the entrepreneurial competences developed by HEIs and BSIs and were demanded (considered as important) by the market in the researched countries. Further, we developed the entrepreneurship training methodology for transdisciplinary students to enhance entrepreneurial competence dissemination and development across education programs and beyond.
Keywords: 650; business supporting institutions (BSIs); competence; entrepreneurial competences; higher education institutions (HEIs); managerial competences